Low Carbon Energy Democracy in the Global South? - Campbell, Ben; Cloke, Jon; Brown, Ed (Routledge, 2021)
Social science tools and practitioner experiences help to understand relations of democratic processes to low carbon energy transitions in the Global South. This requires interrogating Euro-centric assumptions about participation, national development, and infrastructure models in conditions of inequality and state capture. Issues of historical extractive energy injustice and the asymmetries of Southern climate vulnerability as compared to Northern GHG emission sources, drag this topic into political focus for questioning the models of mass consumption that have driven economic development over two centuries. Can democracy be reinvented with renewables?
EPrint Processing Status: Full text deposited in DRO